2016
DOI: 10.1039/c6nj00921b
|View full text |Cite
|
Sign up to set email alerts
|

The healing of B- or N-vacancy defective BNNTs by using CO molecule: a DFT study

Abstract: Boron or nitrogen vacancies of BNNTs can be effectively healed by CO at ambient temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
(68 reference statements)
1
5
0
Order By: Relevance
“…On the other hand, the B1B3 and B2B3 binding distances in the nine‐membered ring increases from 2.49 Å in the pristine BNNT to 2.54 Å in the defected tube (Figure ). These bond distances are consistent with those other related studies . The NBO atomic charge over B1, B2, and B3 is calculated to be 0.71, 0.71, and 1.03 e, respectively, suggesting that the B3 atom is the main active site over N V ‐BNNT.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…On the other hand, the B1B3 and B2B3 binding distances in the nine‐membered ring increases from 2.49 Å in the pristine BNNT to 2.54 Å in the defected tube (Figure ). These bond distances are consistent with those other related studies . The NBO atomic charge over B1, B2, and B3 is calculated to be 0.71, 0.71, and 1.03 e, respectively, suggesting that the B3 atom is the main active site over N V ‐BNNT.…”
Section: Resultssupporting
confidence: 91%
“…As noted earlier, the formation of the N‐vacancy is easier than that of the B‐vacancy over BNNSs and BNNTs surface . To investigate the dependency of the defect formation energy on the curvature of the BNNS, we calculate the formation energy ( E f ) of the N V ‐BNNS and N V ‐BNNT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ahmadi et al reported the values of energy gap and B-N bond length for BNNS 5.93 eV and 1.45 Å, respectively, and for Al-doped BNNS the band gap as well as Al-N bond length are 5.39 eVand 1.74 Å, respectively [34]BNNS is also a very successful nanosorbent and has been studied in many theoretical studies to detect H2O [35] NO [36] , CO [37] , CH2O [38], COCl2 [39], C2H4 [40], and N2O [41]. This nanosheet and metal decorated BNNS have also been used in the manufacture of many electronic devices [42][43][44][45][46][47][48]. It can also be used as a valuable material in the coating industry and metal protection because it is impermeable to gases and liquids and is also an electrical insulator [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%